2003
DOI: 10.1021/ja028574m
|View full text |Cite
|
Sign up to set email alerts
|

Directed Denaturation:  Room Temperature and Stoichiometric Unfolding of Cytochrome c by a Metalloporphyrin Dimer

Abstract: Using circular dichroism, UV-vis, and trypsin proteolysis, we have shown how a metalloporphyrin dimer induces the unfolding of a protein, cytochrome c, under physiologically relevant conditions and accelerates its rate of proteolytic degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 13 publications
2
41
0
1
Order By: Relevance
“…154 A change in the binding with a change from a 1:1 binding to a 2:1 (protein:complex) stoichiometry was observed on increasing the temperature from 25 to 70 °C. This result in particular adds to the original conceptual observation from the Hamilton group, 128 in that it implies negative co-operative binding to the unfolded form of Cyt c is favoured.…”
Section: M(bpy)3 Scaffolds For Multipoint Surface Recognitionsupporting
confidence: 62%
“…154 A change in the binding with a change from a 1:1 binding to a 2:1 (protein:complex) stoichiometry was observed on increasing the temperature from 25 to 70 °C. This result in particular adds to the original conceptual observation from the Hamilton group, 128 in that it implies negative co-operative binding to the unfolded form of Cyt c is favoured.…”
Section: M(bpy)3 Scaffolds For Multipoint Surface Recognitionsupporting
confidence: 62%
“…Hamilton and coworkers showed that Cu(II)-porphyrins, which are believed to exist as dimers in aqueous solution, lowered the temperature at which cytochrome c undergoes denaturation (T M ) by ∼50 • C, as determined by UV absorbance and CD [116]. In subsequent work, Hamilton et al characterized polyanionic Cu(II)-porphyrin dimer mediated catalysis of the denaturation-mediated proteolysis of cytochrome c under physiological conditions by natural proteases (19, Fig.…”
Section: Cu(ii) Coordination Complex Mediated Protein Denaturationmentioning
confidence: 99%
“…Because the melting point of cytochrome c in the presence of the tetrabiphenylporphyrinbased receptor is influenced by ionic strength, electrostatic interactions contribute to the complexation. Metalloporphyrin derivatives have also been prepared for complexation with cytochrome c [109], and dimeric Cu(II)-porphyrins were effective for denaturation.…”
Section: Recognition Of Proteins Using Tpp Derivativesmentioning
confidence: 99%
“…Complexation with the copper TPP derivatives accelerates denaturation and proteolytic degradation of heme proteins with trypsin [109][110][111]. In the presence of four equivalents of the dimeric Cu(II)-porphyrin, tryptic digestion of cytochrome c was advanced compared with the porphyrin free condition.…”
Section: Recognition Of Proteins Using Tpp Derivativesmentioning
confidence: 99%
See 1 more Smart Citation